He runs, she runs : why gender stereotypes do not harm women candidates - Brooks, Deborah Jordan (ACLS Humanities E-Book., 2013)
"While there are far more women in public office today than in previous eras, women are still vastly underrepresented in this area relative to men. Conventional wisdom suggests that a key reason is because female candidates start out at a disadvantage with the public, compared to male candidates, and then face higher standards for their behavior and qualifications as they campaign. He Runs, She Runs is the first comprehensive study of these dynamics and demonstrates that the conventional wisdom is wrong. With rich contextual background and a wealth of findings, Deborah Jordan Brooks examines whether various behaviors--such as crying, acting tough, displays of anger, or knowledge gaffes--by male and female political candidates are regarded differently by the public. Refuting the idea of double standards in campaigns, Brooks's overall analysis indicates that female candidates do not get penalized disproportionately for various behaviors, nor do they face any double bind regarding femininity and toughness. Brooks also reveals that before campaigning begins, women do not start out at a disadvantage due to gender stereotypes. In fact, Brooks shows that people only make gendered assumptions about candidates who are new to politics, and those stereotypes benefit, rather than hurt, women candidates. Proving that it is no more challenging for female political candidates today to win over the public than it is for their male counterparts, He Runs, She Runs makes clear that we need to look beyond public attitudes to understand why more women are not in office"--Publisher's description.